DESIGN OF A 100 KG CAPACITY WORKING LIFT CART FOR SMALL-SCALE INDUSTRIAL APPLICATIONS - Apriandi, Riyki; Rahmany, Rijal Surya (ROTOR, 2024)
To accommodate heavy tool movement, forklifts are commonly used. However, a forklift is too large for use in confined workspaces within small industries. Therefore, it is proposed that a 'Working Lift Cart' be designed with a compact size. This research aims to design and develop a compact lift cart that offers flexible movement and reduces operational risks compared to existing forklift products. The method employed in this research involves a direct analysis of two proposed product plan concepts. The proposed concepts are selected based on a needs analysis. The chosen concept undergoes a safety risk analysis from the operator's perspective using the RULA method, while the product design is subjected to static stress analysis on the frame and the lifter. The results indicate that the second concept, with greater operational flexibility, is chosen. The RULA analysis, conducted using CATIA software, indicates that operating with a remote controller is significantly safer and less prone to injury. However, manual operation is retained for usability purposes. The analysis of the frame structure and lifter shows that the proposed design is safe for a 100 kg load on the lifter. Keywords: Working Lift Cart, Design, RULA, Static Stress Analysis